Organogênese in vitro de explantes juvenis de Toona ciliata var. Australis - Romaniuk, Marina de Souza (2021)
The Australian Red Cedar (Toona ciliata M. Roem. var. australis) is a species of the Meliaceae family with great economic and environmental potential since it has fast growth, reaching up to 30 meters in height and resistance to the cedar borer (Hypsipyla grandella Zeller), besides producing secondary metabolites widely used in medicine in treatments for diseases such as diabetes, arthritis, depression, and cancer. However, a limiting factor is its seminal propagation since the complexity of harvesting and the short viability of seeds, being the micropropagation an alternative to propagate the species. The aim of this study was to evaluate the morphogenesis of juvenile explants of Australian cedar cultivated in culture medium with different concentrations of TDZ and BAP, and the multiplication of the regenerated organs. Two independent experiments were carried out, one with culture medium constituted by TDZ and the other by BAP, using as plant material for both experiments hypocotyl, leaf and root explants, being cultivated in MS medium with different concentrations of TDZ (0.0, 0.25, 0.5 and 1.0 mg. L-1) and BAP (0.0, 0.1, 0.5 and 1.0 mg. L-1). In both experiments direct organogenesis was evaluated, counting the percentage of regenerated explants and multiplication rate, counting how many sprouts were formed on a single explant and indirect organogenesis, were considered the characteristics of oxidation, texture, color, intensity and region of the formed callus The sprouts were subcultivated three times in MS medium + 0.3 mg. L-1 BAP + 0.01 mg. L-1 ANA and later transplanted twice in Agrinobre® substrate, performing at transplanting the biometry evaluations.. Cultivation in medium with different concentrations of TDZ induced regeneration in 43.8% of the hypocotyl segments under the concentration of 0.25 mg. L-1 TDZ. There was indirect organogenesis in 94.4% of the hypocotyl explants, of these 85.5% were at concentration of 1.0 mg. L-1 TDZ, with a predominance of semi-compact texture and white coloration. The concentration 0.5 mg. L-1 TDZ had the greatest formation of friable callus. Considering the experiment with BAP was observed direct organogenesis in 95% of explants from hypocotyl, cultivated in medium with a concentration of 0.5 mg. L-1. At 90 days of culture, the greatest number of sprouts per explant was in the 0.1 mg. L-1 BAP with a multiplication rate of 1.66. The sprouts at 180 days had the greatest height growth (56.8 mm) and rooting percentage (34.14%) in the concentration 0.5 mg. L-1 BAP. At 240 days the sprouts formed in 1.0 mg. L-1 BAP developed greater growth in total height with 142.0 mm and rooting percentage of 63.15%. The utilization of BAP and TDZ in the organogenesis of juvenile explants of T. ciliata provided advance regarding the effects of bioregulators and the morphological responses of each explant, demonstrating which are more propitious for the propagation of this species, besides serving as a line for future researches.